Test-retest, intra- and inter-rater reliability of the reactive balance test in patients with chronic ankle instability - Maricot, Alexandre; Lathouwers, Elke; Verschueren, Jo; De Pauw, Kevin; Meeusen, Romain; Roelands, Bart; Tassignon, Bruno (Frontiers in Neurology, 2024)
Introduction The Reactive Balance Test (RBT) could be a valuable addition to research on chronic ankle instability (CAI) and clinical practice, but before it can be used in clinical practice it needs to be reliable. It has already been proven reliable in healthy recreational athletes, but not yet in patients with CAI who have shown persistent deficits in dynamic balance. The study aimed to determine the test-retest, intra-, and inter-rater reliability of the RBT in patients with CAI, and the test-retest and inter-rater reliability of the newly developed RBT score sheet. Methods We used a repeated-measures, single-group design to administer the RBT to CAI patients on three occasions, scored by multiple raters. We included 27 participants with CAI. The study used multiple reliability measures, including Pearson r, intra-class correlations (ICC), standard error of measurement (SEM), standard error of prediction (SEP), minimal detectable change (MDC), and Bland–Altman plots, to evaluate the reliability of the RBT’s outcome measures (visuomotor response time and accuracy). It also assessed the test-retest and inter-rater reliability of the RBT score sheet using the same measures. Results The ICC measures for test-retest reliability were similar for accuracy (0.609) and VMRT (0.594). Intra-rater reliability had high correlations and ICCs for accuracy (r = 0.816, ICC = 0.815) and VMRT (r = 0.802, ICC = 0.800). Inter-rater reliability had a higher ICC for VMRT (0.868) than for accuracy (0.690). Conclusion Test-retest reliability was moderate, intra-rater reliability was good, and inter-rater reliability showed moderate reliability for accuracy and good reliability for VMRT. Additionally, the RBT shows robust SEM and mean difference measures. The score sheet method also demonstrated moderate test-retest reliability, while inter-rater reliability was good to excellent. This suggests that the RBT can be a valuable tool in assessing and monitoring balance in patients with CAI.